Punitive Attitudes Toward Sex Offenders: Do Moral Panics Cause Community Members to Be More Punitive? - Klein, Jennifer L. (Criminal justice policy review, 2019)
Researchers interested in registered sex offenders (RSOs) and sex offender registration and community notification laws (SORN) legislation have noted that there is a perpetual moral panic associated with the topic. Community members frequently call for increased crime control policies to monitor RSOs, despite the research suggesting these laws do not effectively reduce recidivism levels for this offender group. The current study seeks to predict participant support for punitive change to the registry and SORN legislation, based on the idea that a perpetual moral panic continuously exists concerning RSOs. Using a stepwise ordinary least squares (OLS) regression analytical approach, the findings suggest that the theoretical elements of a moral panic are strongly predictive of punitive support and mediate other predictor variables normally associated with punitive attitudes toward sex offenders and the sex offender registry.